The political economy of the environment - Boyce, James K.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2002)
In a provocative and original analysis, James K. Boyce examines the dynamics of environmental degradation in terms of the balances of power between the winners and the losers. He provides evidence that inequalities of power and wealth affect not only the distribution of environmental costs, but also their overall magnitude: greater inequalities result in more environmental degradation. Democratization--movement toward a more equitable distribution of power--therefore is not only a worthwhile objective in its own right, but also an important means toward the social goals of environmental protection and sustainable development.
1. Stealing the commons -- 2. Let them eat risk? -- 3. Investing in natural and human capital -- 4. Inequality as a cause of environmental degradation -- 5. Rethinking the environmental kuznets curve -- 6. Power distribution, the environment, and public health -- 7. The globalization of market failure? -- 8. A squandered inheritance -- 9. Democratizing environmental ownership.
Includes bibliographical references and indexes.
Keywords: Environmental economics; Electronic books